Basking shark breaching behaviour observations West of Shetland - Hayes, E; Godley, BJ; Nimak-Wood, M; Witt, MJ (Marine Biodiversity Records, 2018)
This is the author accepted manuscript. The final version is available from BioMed Central via the DOI in this record. This study reports observations of basking sharks (Cetorhinus maximus) sighted during an offshore geophysical survey conducted in July and August 2013, west of Shetland, UK. During the 38-day survey, trained and dedicated marine wildlife observers recorded 19 sightings of basking sharks (n=22 individuals). Of these observations, 17 were of single sharks, with one observation of two sharks and one observation of three sharks. All surface sightings occurred in water with depths between 129 and 199 m, predominantly prior to noon local time (79%), and were mostly of sharks 6-8 m in length, although a young (2 m) individual was also recorded. Breaching behaviour was observed on 14 occasions, by individuals or in small groups. Breaching has been proposed as a male-male competitive behaviour during courtship displays and female basking sharks may breach to signal their readiness for mating. Aggregations of basking sharks at frontal systems are well documented and linked to the occurrence of prey patches; however, these oceanographic features may also be of importance to courtship. The high number of sightings of sharks recorded during a relatively short time frame in addition to breaching behaviour and presence of young individuals, suggest that this area west of Shetland may be an important habitat for the basking shark.